Vision Based Human Decoy System for Spot Cooling - Tan Chun Hou; Wan Nurshazwani Wan Zakaria; Tai Sue Jing; Razali Tomari; Tee Kian Sek; Anis Azwani Muhd Suberi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This project aims to reduce the energy consumption of air conditioner usage while maintaining occupant comfort. Cooling down the unoccupied space can be considered as waste of energy. Therefore, a human decoy system is proposed to track any human in the detection area. Image contains depth data in each pixel which can be used to detect the presence of target subject as well as their position. The acquired position data is processed by using MATLAB and subsequently is transmitted to Arduino Mega using serial communication to control stepper motors. The experimental results show that the air conditioner airflow is successfully can be directed to the target human subject with average response of 0.860 seconds per movement within detection area.